2016
DOI: 10.1080/10410236.2016.1196423
|View full text |Cite
|
Sign up to set email alerts
|

Social Inclusion Predicts Lower Blood Glucose and Low-Density Lipoproteins in Healthy Adults

Abstract: Loneliness has been shown to have direct effects on one's personal well-being. Specifically, a greater feeling of loneliness is associated with negative mental health outcomes, negative health behaviors, and an increased likelihood of premature mortality. Using the neuroendocrine hypothesis, we expected social inclusion to predict decreases in both blood glucose levels and low-density lipoproteins (LDLs) and increases in high-density lipoproteins (HDLs). Fifty-two healthy adults provided self-report data for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 19 publications
0
7
0
1
Order By: Relevance
“…A very recent report on older adults indicates that the inclusion of planning to enhance social support is essential to diminishing depressive symptoms in older adults with type 2 diabetes [38]. Higher levels of social inclusion have been reported as predictive of lower levels of blood glucose and low-density lipoprotein [39], and it has been reported that low social support is linked to shorter leukocyte telomere length which is a predictor for higher rates of cellular aging [40]. In addition, since it is now known that the trajectory of social support is predictive of functional disability in adults with type 2 diabetes [41], the logical conclusion can be drawn that social support is integral to coping and should be included in future studies designed to build knowledge on coping in adults with type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…A very recent report on older adults indicates that the inclusion of planning to enhance social support is essential to diminishing depressive symptoms in older adults with type 2 diabetes [38]. Higher levels of social inclusion have been reported as predictive of lower levels of blood glucose and low-density lipoprotein [39], and it has been reported that low social support is linked to shorter leukocyte telomere length which is a predictor for higher rates of cellular aging [40]. In addition, since it is now known that the trajectory of social support is predictive of functional disability in adults with type 2 diabetes [41], the logical conclusion can be drawn that social support is integral to coping and should be included in future studies designed to build knowledge on coping in adults with type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Social inclusion is an emerging construct that researchers are seeking to better understand given evidence for its relationship to health/well‐being (Floyd et al, ). Social inclusion has been defined as the experience of acceptance/belonging through opportunities to participate in valued social activities (Social Inclusion Unit, ).…”
Section: Introductionmentioning
confidence: 99%
“…Social inclusion has important and beneficial implications for health, well-being, and quality of life (Floyd et al, 2017; Levitas et al, 2007). Socially excluded individuals place a significant burden on society, with socioeconomic consequences for government, community, and familial supports.…”
mentioning
confidence: 99%